Development of enzyme linked immunosorbent assay (ELISA) to detect antibodies to Pseudomonas aeruginosa cell surface antigens in sera of patients with cystic fibrosis. Issue 10 (October 1986) - Brett, M M; Ghoneim, A T; Littlewood, J M; Losowsky, M S
Abstract : An enzyme linked immunosorbent assay (ELISA) to measure free serum IgG antibodies to Pseudomonas aeruginosa in patients with cystic fibrosis was developed. Seven strains of P aeruginosa cells, treated with glutaraldehyde and representing the most commonly isolated serotypes in our cystic fibrosis unit, were used. The specificity of the test was confirmed by the absence of cross reacting antibodies to other Gram negative bacteria. The results showed differences in the titres of antibodies at different stages of P aeruginosa infection. Because of its reproducibility, specificity, and sensitivity these preliminary results suggest that this test may be of value in monitoring the progress of P aeruginosa infection in patients with cystic fibrosis.